1994
DOI: 10.1182/blood.v84.8.2506.2506
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha (TNF alpha) downregulates c-kit proto- oncogene product expression in normal and acute myeloid leukemia CD34+ cells via p55 TNF alpha receptors

Abstract: Tumor necrosis factor alpha (TNF alpha), as a modulator of hematopoiesis, interacts with many growth factor receptors, such as interleukin-3, granulocyte-macrophage colony-stimulating factor (CSF), and granulocyte-CSF receptors. Here, we studied the interactions between TNF alpha and the stem cell factor (SCF) receptor, c-kit, in normal CD34+ hematopoietic progenitors and their leukemic counterpart, ie, acute myeloid leukemic (AML) CD34+ cells coexpressing c-kit antigen. The results showed that (1) incubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Our results indicate that the enhancing effects of TNFon IL-3 or GM-CSF-induced AML cell growth are equally mediated through both the p55 and p75 TNF receptors, whereas the inhibition of G-CSF or SCF-stimulated proliferation is exclusively signalled via the p55 receptors. These data concerning the TNF-induced inhibition of the G-CSF or SCFinduced proliferation of AML cells are in accordance with reported observations (Delwel et al, 1992;Khoury et al, 1994). However, a recent study has shown that the TNFmediated enhancement of IL-3/GM-CSF-induced proliferation is only a p55-mediated event (Delwel et al, 1992).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicate that the enhancing effects of TNFon IL-3 or GM-CSF-induced AML cell growth are equally mediated through both the p55 and p75 TNF receptors, whereas the inhibition of G-CSF or SCF-stimulated proliferation is exclusively signalled via the p55 receptors. These data concerning the TNF-induced inhibition of the G-CSF or SCFinduced proliferation of AML cells are in accordance with reported observations (Delwel et al, 1992;Khoury et al, 1994). However, a recent study has shown that the TNFmediated enhancement of IL-3/GM-CSF-induced proliferation is only a p55-mediated event (Delwel et al, 1992).…”
Section: Discussionsupporting
confidence: 92%
“…Proliferationof acute myeloid leukaemia (AML) cells in vitro is stimulated by haemopoietic growth factors (HGFs), in particular, interleukin-3 (IL-3), granulocytemacrophage colony-stimulating factor (GM-CSF), granulocyte-CSF (G-CSF), macrophage-CSF (M-CSF) and stem cell factor (SCF) (Delwel et al, 1988;Kuriu et al, 1991). Tumournecrosis factor-(TNF-) can modulate the in vitro responses through a variety of mechanisms, including synergism with IL-3 and GM-CSF in stimulation of AML growth (Hoang et al, 1989), and up-regulation of IL-3 and GM-CSF receptors (Elbaz et al, 1991a); suppression of G-CSF-induced AML proliferation through down-regulation of G-CSF receptors (Elbaz et al, 1991b); inhibition of SCF-stimulated AML cell growth by down-regulation of SCF receptors (Khoury et al, 1994); induction of AML cell growth via an autocrine mechanism (Carter et al, 1992); and inhibition of clonal proliferation of leukaemic cells . Some AML cells constitutively secrete TNFand use this activity as an autocrine growth modulator (Oster et al, 1989;Carter et al, 1992).…”
mentioning
confidence: 99%
“…However, only a small but steady number of CD34 + /c-kit <low cells were detected in the CB, suggesting that a niche constructed by stromal cells or some cytokine(s) negatively regulate the induction of c-kit molecules and the reactivity to SCF to maintain dormant P-HSCs. The report that TNF-α and TGF-β downregulate not only the c-kit m-RNA but also c-kit protein in CD34 + /c-kit high cells and CD34 + leukemia cells might support this possibility [38][39][40].…”
Section: Rh123 Efflux From Cd34 + /C-kitmentioning
confidence: 90%
“…Experimental evidence suggests that tumour necrosis factor (TNF) is involved in the proliferation of acute leukaemia cells ( Hoang et al , 1989 ; Oster et al , 1989 ; Elbaz et al , 1991a , b; Delwel et al , 1992 ; Carter et al , 1994 , 1996). TNF acts as a pleiotropic cytokine enhancing leukaemic growth ( Hoang et al , 1989 ; Oster et al , 1989 ; Carter et al , 1994 , 1996), inducing the transcription of other proliferation‐relevant cytokine or cytokine receptor genes ( Elbaz et al , 1991a , b; Delwel et al , 1992 ; Vinante et al , 1993 , 1996; Khoury et al , 1994 ; Carter et al , 1996 ) and triggering apoptosis ( Elbaz et al , 1991b ; Delwel et al , 1992 ; Khoury et al , 1994 ; Carter et al , 1996 ).…”
mentioning
confidence: 99%
“…Both TNF receptors (p55‐ and p75‐TNFR), which bind to TNF with roughly equal affinity ( Bazzoni & Beutler, 1995; Gruss & Dower, 1995), have been reported to be expressed on acute leukaemia cells and to mediate distinct either inhibitory or stimulatory effects ( Delwel et al , 1992 ; Carter et al , 1996 ). In acute myeloid leukaemia (AML) blasts the engagement in vitro of p55‐TNFR can be followed by enhanced DNA synthesis ( Hoang et al , 1989 ; Oster et al , 1989 ; Delwel et al , 1992 ; Carter et al , 1994 , 1996), induction of granulocyte‐macrophage colony stimulating factor (GM‐CSF) ( Carter et al , 1996 ) and regulation of the receptors for stem cell factor (SCF), granulocyte colony stimulating factor (G‐CSF) and GM‐CSF ( Elbaz et al , 1991a , b; Delwel et al , 1992 ; Khoury et al , 1994 ; Carter et al , 1996 ) and by cytotoxic effects ( Kobayashi et al , 1997 ). p75‐TNFR seems to be mainly involved in the induction of secondary cytokines ( Delwel et al , 1992 ; Carter et al , 1996 ).…”
mentioning
confidence: 99%